The Empire's New Clothes
This chilling feature, shot by WITNESS partner Jimmie Briggs, tells the story of Acholi school girls from St. Mary's College in Northern Uganda who were abducted by the Lord's Resistance Army to serve as child soldiers. Of the 250,000 child soldiers worldwide, many are used as sexual servants, spies, porters and frontline grunts. These unwilling combatants often find themselves subject to disease, physical assault and rape. Witness interviews one of the girls who escaped and survived the ordeal, and a teacher and assistant headmistress at St. Mary's College. The headmistress, Sister Rachele Fassera, recounts the night of her students' abduction and the torturous process of trying to secure their release. Music by Philip Glass.